Functional traits and adaptive capacity of European forests to climate change - Bussotti, Filippo; Pollastrini, Martina; Holland, Vera; Brüggemann, Wolfgang (Environmental and Experimental Botany, 2014)
Increasing temperatures and drought risks through climate change are expected to have several consequences for European forests. Adaptive strategies may include: (i) persistence of the current forest types, thanks to the acclimatization to local conditions and to phenotypic plasticity of the populations; (ii) evolution, or local adaptation, i.e., change in genotype (frequencies) within the same species due to environmental pressure. It is favored by large within population diversity and (when possible) gene flow among populations; (iii) migration and substitution of species; and (iv) extinction of populations with low ecological plasticity, especially at the edges of their distribution or in the case of isolated (relict) populations. Because of the economic and ecological relevance of forests, it is of fundamental importance to apply appropriate forest management to make forests able to cope with the new environmental conditions. This may include changes in the composition and structure of forest stands, selection of adapted provenances of the most important European tree species or, if this is regarded as insufficient, assisted migration (i.e., the use of species suitable for the future climatic conditions) and, alternatively, substitution of native with non native species. The intraspecific (genetic and phenotypic) variability at a given site has been proven to be often higher than the variability among sites. Species with a large distribution range are supposed to have a wide variety of genotypes, allowing them to be adapted to different environmental conditions. Genetic variability and phenotypic plasticity are the key factors for the identification of useful tree genotypes for future forestation programs. Adaptation to drought, i.e., the probably most important future abiotic risk factor for forestry, can be reflected in variation of key functional traits (FT), at morphological, physiological and phenological level. FT utilized to screen for adapted genotypes in common gardens and provenance trials include growth, survival, leaf flushing and senescence, foliar features as leaf mass per area and nitrogen content, water use efficiency (e.g., estimated by analysis of the stable carbon isotopes, d13C) chlorophyll content, photosystem II functioning, and photosynthetic capacity under water shortage. Current modeled simulation of future forest distribution suggests the expansion of forests at the highest latitudes and altitudes, alongside with a reduction in the hottest and driest Mediterranean regions of South Europe. The general expectations, however, may be disproved especially at a regional level, by factors unexpected or not well known, such as possible extreme climatic events and increased roles of parasites/diseases (with negative effects), or high capacity of forest persistence or adaptation (with positive effects). Natural migration and species substitution can be hampered by co-factors of climate change, such as forest fragmentation and increased frequency and intensity of forest fires.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Adaptation; Extinction; functional traits; Local evolution; migration; Phenotypic plasticity; Phenotyping; provenances

QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

The likely impact of climate change on the biodiversity of Italian forests - Borghetti, M.; La Mantia, T.; Menozzi, P.; Piotti, a (Forest@ - Rivista di Selvicoltura ed Ecologia Forestale, 2012)
Keywords: 2012; 245-250; 9; Adaptation; biodiversità delle foreste italiane; Biodiversity; borghetti m; citation; climate change; climatico sulla; contents; FOREST; http; impact; it; Italy; la mantia t; menozzi p; online 2012-11-19; piotti a; probabili impatti del cambiamento; sisef; url; www

Seasonal evolution of water status after outplanting of two provenances of Holm oak nursery seedlings - Andivia, Enrique; Carevic, Felipe; FERNÁNDEZ, MANUEL; Alejano, Reyes; VÁZQUEZ-PIQUÉ, JAVIER; TAPIAS, RAÚL (New Forests, 2012)
Forest restoration programs using Holm oak (Quercus ilex ssp. ballota [Desf.] Samp.) have had limited success. The effect of plant provenance on plantation success is uncertain, although some previous studies suggest that some provenances may be better able to tolerate stress. We studied the tolerance to drought in seedlings from two Spanish provenances of Holm oak before and after outplanting. One provenance was from a continental climate with cold winters (GR) and the other was from a xeric climate (HU). Seedlings were subjected to a water stress test in the nursery during the summer and survival was visually assessed after 2 weeks. In addition, 35 healthy seedlings of each provenance that were not subjected to the water stress tests were used for outplanting experiment. In these plants the seasonal changes in water potential at dawn (W), speciﬁc leaf area (SLA), cuticular transpiration (Ec ), and loss of xylem hydraulic conductance of twigs (PLC) were measured over 18 months. After the water stress test in summer, mortality was 44.3 % for GR seedlings and 12.6 % for HU seedlings. In addition there were differences between the two provenances in plant water status after planting. The HU provenance had a better water status and was more water conservative in the summer (higher W, lower Ec , lower PLC), but not in the winter. The different drought tolerance and water relations parameters of these two provenances indicate that provenance should be considered in forest restoration and conservation programs involving Holm oak.
Keywords: Adaptation; Drought; Field performance; Physiological traits; water stress

Two provenances of Quercus ilex ssp. ballota (Desf) Samp. nursery seedlings have different response to frost tolerance and autumn fertilization - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER; Alejano, Reyes (European Journal of Forest Research, 2011)
Despite evidences that Holm oak has a high plasticity and great adaptability, there is limited or contradictory knowledge of the morphological and physiological variability of this species. Holm oak has been widely used for reforestation projects in Mediterranean areas, but has frequently shown poor ﬁeld performance. We hypothesized that Holm oak has inter-population differences in physiological responses to abiotic stressors that could affect reforestation success. The inﬂuence of nursery culture on the characteristics of Holm oaks from different provenances has not been explored in depth. Thus, we studied the effect of nursery autumn fertilization on morphological traits, frost tolerance, root growth potential, and nutritional status of two Spanish provenances of Holm oak, La Alcarria (a region with inland Mediterranean climate) and Sierra Morena Occidental (a region with a warm coastal Mediterranean climate). There were signiﬁcant differences between the provenances in frost tolerance, biomass allocation, and leaf nutrient content, suggesting a role of genetic factors. The leaves of seedlings from La Alcarria had less visual damage at -12C than seedlings from the warmer provenance (45% vs. 92%). Seedlings from La Alcarria, compared to those from Sierra Morena, had higher leaf P concentration (0.17% vs. 0.15%), greater stem diameter (3.1 mm vs. 2.7 mm), lower shoot-to-root dry mass ratio (0.46 vs. 0.53), and lower slenderness (4.03 vs. 5.31). For both provenances, N autumn fertilization improved growth, root growth potential, cold hardiness, and nutritional status of seedlings. We suggest that forest reforestation programs should consider to a greater extent Holm oak provenances and their tolerances to different abiotic stressors.
Keywords: á autumn fertilization; á reforestation á; Adaptation; adaptation á cold hardiness; Autumn fertilization; Cold hardiness; Holm oak; holm oak á provenance; provenance; Reforestation

Natural selection on cork oak: allele frequency reveals divergent selection in cork oak populations along a temperature cline - Ramírez-Valiente, J. a; Lorenzo, Z.; Soto, A.; Valladares, F.; Gil, L.; Aranda, I. (Evolutionary Ecology, 2010)
A recent study of population divergence at neutral markers and adaptive traits in cork oak has observed an association between genetic distances at locus QpZAG46 and genetic distances for leaf size and growth. In that study it was proposed that certain loci could be linked to genes encoding for adaptive traits in cork oak and, thus, could be used in adaptation studies. In order to investigate this hypothesis, here we (1) looked for associations between molecular markers and a set of adaptive traits in cork oak, and (2) explored the effects of the climate on among-population patterns in adaptive traits and molecular markers. For this purpose, we chose 9-year-old plants originating from thirteen populations spanning a broad range of climatic conditions. Plants established in a common garden site were genotyped at six nuclear microsatellites and phenotypically characterized for six functional traits potentially related to plant performance. Our results supported the proposed linkage between locus QpZAG46 and genes encoding for leaf size and growth. Temperature caused adaptive population divergence in leaf size and growth, which was expressed as differences in the frequencies of the alleles at locus QpZAG46.
Keywords: Adaptation; Additive effects; Dominance; Natural selection; Overdominance; Quercus suber

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D.; Rodríguez, J.; Sanz, J. M.; Merino, J. (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
The following values have no corresponding Zotero field: accession-num: 9626534
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology